Optimized Prediction of Weapon Effectiveness in BVR Air Combat Scenarios Using Enhanced Regression Models - Andre R. Kuroswiski; Annie S. Wu; Angelo Passaro (IEEE Access)
This study investigates high-performance models for predicting the Weapon Engagement Zone (WEZ) in beyond-visual-range (BVR) air combat scenarios. Accurate WEZ predictions are crucial for decision-making in air combat, and high-performance solutions are essential for developing and deploying autonomous systems. To optimize the model training process, we introduce novel feature engineering and data augmentation strategies, achieving a 70% improvement in the Mean Absolute Error (MAE) of WEZ predictions. A comparison of various regression methods highlights the potential of polynomial-based alternatives when fully utilized. In our evaluations, Polynomial Regression (PR) with higher interaction degrees outperforms more complex machine learning models in prediction accuracy and computational efficiency. For instance, Lasso regression, a PR method with regularization, achieves results that are 33% better and 2.1 times faster than the best artificial neural network-based solution. Our results challenge common assumptions in the literature about the complexity and feasibility of higher-order PR solutions, suggesting that they can be a compelling alternative for various challenges across domains. This study also provides a new open dataset to facilitate further research and advancements in this field.